How close are we to storing data in DNA? - Gervasio, Joao Henrique Diniz Brandao; da Costa Oliveira, Henrique; da Costa Martins, Andre Guilherme; Pesquero, Joao Bosco; Verona, Bruno Marinaro; Cerize, Natalia Neto Pereira (Trends in biotechnology (Regular ed.), 2024)
DNA is a more efficient and long-lasting data storage method. It offers better compression, higher physical density, longer stability, and lower energetic cost than traditional digital methods. Metadata should be embedded in the DNA sequence.Biocybersecurity must be prioritized to prevent attacks with synthetic DNA that could encode malware triggered during DNA sequence analysis.Standardization of the coding and decoding process is necessary for long-term accessibility. Errors in methodology can lead to data loss, emphasizing the need for a reliable protocol for handling samples.Inclusion of identifying features in the DNA is crucial for future recognition of it as data storage. Markers or sequences can indicate that the DNA is synthetic, not biological. This ensures that future generations can recognize and access the stored data even if knowledge of DNA data storage is lost. DNA is an intelligent data storage medium due to its stability and high density. It has been used by nature for over 3.5 billion years. Compared with traditional methods, DNA offers better compression and physical density. DNA can retain information for thousands of years. However, challenges exist in scalability, standardization, metadata gathering, biocybersecurity, and specialized tools. Addressing these challenges is crucial for widespread implementation. Collaboration among experts, as well as keeping the future in mind, is needed to unlock the full potential of DNA data storage, which promises low energy costs, high-density storage, and long-term stability. DNA is an intelligent data storage medium due to its stability and high density. It has been used by nature for over 3.5 billion years. Compared with traditional methods, DNA offers better compression and physical density. DNA can retain information for thousands of years. However, challenges exist in scalability, standardization, metadata gathering, biocybersecurity, and specialized tools. Addressing these challenges is crucial for widespread implementation. Collaboration among experts, as well as keeping the future in mind, is needed to unlock the full potential of DNA data storage, which promises low energy costs, high-density storage, and long-term stability.